Synthesis, Characterization, and Crystal Structures of Bis-Imidazolium Salts and Respective Dinuclear Ag(I) N-Heterocyclic Carbene Complexes: In Vitro Anticancer Studies against “Human Colon Cancer” and “Breast Cancer” - Rosenani A. Haque; Siti Fatimah Nasri; Muhammad Adnan Iqbal; Sawsan S. Al-Rawi; Seyedeh Fatemeh Jafari; Mohamed B. Khadeer Ahamed; A. M. S. Abdul Majid (Journal of Chemistry)
This paper describes synthesis, characterization (NMR, FT-IR, microanalysis, and X-ray crystallography), in vitro anticancer activity of ortho/para-xylyl linked bis-imidazolium salts (4-5) and respective dinuclear Ag(I) N-heterocyclic carbene (NHC) complexes (6-7). All the compounds were tested for their cytotoxicity against human colorectal cancer (HCT 116) and breast cancer (MCF-7) cell lines. According to cell viability measurements using MTT assay, all the complexes (6-7) showed a dose-dependent cytotoxic activity against both the cell lines, whereas respective salts (4-5) proved to be inactive. The complexes (6-7) demonstrated significant activity with IC50 values range 5.6–20.3 μM for HCT 116 and 1.12–6.38 μM for MCF-7. 5-Fluorouracil was used as standard drug (IC50 = 5.9 μM) for HCT 116, whereas tamoxifen was used as standard drug for MCF-7 (IC50 = 14 μM) cell line.